Comparison of blood pressure and blood glucose level among elderly with non-communicable disease - Ni Putu Wulan Purnama Sari; Jintana Artsanthia (International Journal of Public Health Science (IJPHS), 2019)
Due to increasing age, elderly are prone to non-communicable diseases (NCD), such as hypertension (HT) and diabetes mellitus (DM). Easy physical condition monitoring of people with HT and/or DM is by measuring their blood pressure (BP) and/or blood glucose level (BGL) periodically. This study aimed to compare and analyze the differences of BP and BGL among elderly with HT and/or DM in Bangkok and Surabaya. This cross-sectional study involved 100 and 96 elderly with HT and/or DM in communities of Bangkok and Surabaya respectively (n=196). There were three groups of samples which consisted of 60 DM, 68 HT, and 68 DM&HT cases. Instruments used were demography questionnaire, sphygmomanometer, and glucometer. Test of one-way ANOVA, Least Significant Difference (LSD), Kruskal-Wallis, and Mann-Whitney U were used for data analysis (α<.05). There was a significant difference of systolic and diastolic BP found between groups (p=.000 and p=.011 respectively), but no difference found between the groups of HT and DM&HT (p=.657 and p=.330 respectively). There was a significant difference of BGL found between groups (p=.002), but no difference found between the groups of HT and DM (p=.075) and between the groups of DM and DM&HT (p=.066). BP is significantly different between the group of HT and DM in term of systole and diastole, especially in elderly, but BGL is similar. The risk of being HT for elderly with DM is very high. Elderly with DM&HT have high BP and BGL similarly to those with single disease of HT or DM.